Recursos didácticos y su influencia en el proceso enseñanza aprendizaje de los estudiantes de la unidad educativa Alfonso Reyes Falcón, cantón Simón Bolívar, Provincia Guaya - Villarreal Ortiz, Gregoria Petita (2016)
Most teachers do not develop or interested methodological circumstances that can be applied in the teaching and learning activities of the student, continues to offer the chairs run them through the dictates associated readings, exhibitions, which retains at school in a period of indifference, not consenting to have vision of understanding the topic which gives the class and therefore will not have an excellent academic achievement. It is this situation that led us to conduct this research, taking a sample comprised of 80 students, after completing surveys both teachers and students and the respective analysis, we determined that the teaching resources must always be used to provide all kinds for the best teaching-learning process and it is worrying that the vast majority of the time not used much disinterest on the part of teachers to run the class provided with appropriate educational resources, motivating and attention-grabbing and student interest, hence our proposal to design innovative teaching resources and learning strategies for teaching social studies area, we have games that involve the school, theatrical activity, observation, involved with the surrounding environment and create awareness of our culture and identity both as human beings and to love our country, to promote student learning and increasing their success as students and professionals now and in the future.